Distinctions in Disclosure: Mandated Informed Consent in Abortion and ART. Issue 2 (2015) - Daar, Judith
Abstract : Transparency and disclosure in the health care realm occupy a vital link between the delivery of medical services and patient autonomy. In her article, "Disclosure Two Ways, " Erin Bernstein skillfully explores this link in the context of abortion and assisted conception services, keenly observing the rise in mandatory disclosure laws in both arenas. Her thesis, as I understand it, is that laws that require enhanced disclosure above traditional informed consent thresholds can be understood as neutral tools in the name of patient protection, even — or perhaps especially — when their effect is to persuade a patient to forego the requested treatment. She combats the critique that pre-abortion required disclosures are sui generis, arguing against their uniqueness by analyzing them alongside a swell of mandated disclosure laws in the assisted reproductive technologies (ART) context.